Urgensi Literasi Hukum Bagi Pekerja Migran Indonesia melalui Pendidikan Jarak Jauh - Eny Kusdarini; Chandra Dewi Puspitasari; Sri Wahyu Krida Sakti; Purwaningdyah Murti Wahyuni (Universitas Lampung, 2021)
Protection for migrant workers requires intervention throughout the migration cycle. Moreover, it raises awareness about safe migration before departure, ensuring effective migration policies and mechanisms, ensuring fair recruitment practices, decent working conditions in destination countries, and economic empowerment and reintegration to the home community for retired Indonesian Migrant Workers. However, illegal hiring practices can leave workers trapped in debt-bound situations to go abroad. Often workers are not appropriately trained and do not understand their rights, so they are easily exploited. So the problem arises in this study how to fulfil the legal protection of Indonesian migrant workers? And how can legal literacy improve the protection of Indonesian migrant workers? The study results show that Indonesian migrant workers need state intervention to protect the stage before work, during work, and after work but also need to equip themselves with qualified legal insight. The qualified legal insight will increase the capacity of Indonesian migrant workers and will enable them to face every problem they face. Legal literacy is an urgent matter to be